Meningkatkan Kesadaran Masyarakat Melalui Edukasi Digital Sebagai Pendekatan Baru Dalam Mencegah Wabah Penyakit Mulut dan Kuku - Fajar, Ahmad Choiry; Saputra, Naufal Assani; Pamungkas, Muhammad Rayhan A; Widianingsih, Alia Dhelpina; Inggardini, Aisha; Viona, Dea Okta; Setyaningsih, Annisa; Jagad, Raspati Risang; Elfa, Mardhatillah; Fathurrahman, Muhammad Fauzan; Wahyuningsih, Sri Handari (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The Regular Community Service Program 132 in Jonggrangan, Kulon Progo, focuses on raising public awareness about the prevention of Foot and Mouth Disease Virus (FMDV) through digital education. The main issue faced by the community is the lack of understanding regarding FMDV and its transmission, which impacts the local cattle farming sector. The objective of this program is to provide digital-based education to enhance farmers' and the community's understanding of FMDV prevention and early treatment. The methods used in this program include a qualitative approach with observations, in-depth interviews, group discussions, and direct counseling sessions with farmer groups and the community. The program includes the creation and dissemination of educational videos, e-books, the installation of posters in cattle barns, the development of a land-use map archive for the distribution of cattle barns, green areas, and residential zones in Jonggrangan, as well as training sessions featuring veterinarians as speakers. The results of this program indicate a significant increase in public understanding, with 38 out of 42 farmers stating that they better understand the symptoms and preventive measures of FMDV after participating in the education sessions. Additionally, the land-use map created during this program helps the village government monitor the distribution of cattle barns and design more effective prevention strategies. This initiative has successfully raised community awareness of the importance of barn hygiene and biosecurity procedures, which is expected to reduce the spread of FMDV in the future.